A Detailed Study on impact of SEO on business performance of e-commerce websites - Dr. L Madan Mohan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Since last one decade, competition between various e-commerce websites is seen. This is due to constant addition of new e-commerce companies. E-commerce is nothing but electronically conducted business over networks of computer. The main activities of e-commerce include buying and selling of products, shipping of products and producing financial statements. The relationship between e-commerce and internet marketing is that, internet marketing makes e-commerce website visible to the buyers. Technology and increased use of computers has made marketing global. There is need to be in tune with the new and fast changing trends in field of marketing. Marketing should be customer oriented, alert, positive, forward looking and innovative. SEO is the very basic concept of internet marketing. When people type a keyword in any search engine, multiple lists appears in the search engine result. The order in which the websites appear in the list is controlled by SEO.SEO improves ranking of a particular keyword in search result. When a user enters any keyword in search engine, he finds search result in form of list of sites which are relevant to the keyword. The objective of implementing SEO techniques is higher listing of website in search result than the competitor.